Attention-deficit hyperactivity disorder in ancient Greece: The Obtuse Man of Theophrastus. (June 2018) - Victor, Marcelo M; S da Silva, Bruna; Kappel, Djenifer B; Bau, Claiton HD; Grevet, Eugenio H
We present an ancient Greek description written by the philosopher Theophrastus in his classic book ' Characters ' comparable with modern attention-deficit hyperactivity disorder. The arguments are based in one chapter of this book—The Obtuse Man—presenting features of a character closely resembling the modern description of attention-deficit hyperactivity disorder. In a free comparative exercise, we compared Theophrastus descriptions with modern Diagnostic and Statistical Manual of Mental Disorders (5th ed.; DSM-5) attention-deficit hyperactivity disorder symptoms. The sentences describing The Obtuse Man written by Theophrastus are similar to several symptoms of attention-deficit hyperactivity disorder and he would probably be currently diagnosed with this disorder as an adult. To our knowledge, this is the oldest description compatible with the current conception of attention-deficit hyperactivity disorder in adults in the Western literature. Differently than the moralistic view of ancient Greece regarding those symptoms, the medical attention-deficit hyperactivity disorder conception may be advantageous to patients since it might reduce prejudice and allow individuals to seek treatment.